VALUASI EKONOMI POHON KAYU PUTIH (Melaleuca leucadendron) TERHADAP PEREKONOMIAN DI LPHN TANJUNG BONAI AUR KECAMATAN SUMPUR KUDUS KABUPATEN SIJUNJUNG - Azzahra, Elfira Mukhadiathul; Susilastri, Susilastri; Fakhruzy, Fakhruzy (Ensiklopedia of Journal, 2024)
Eucalyptus oil is a type of essential oil that is widely used as an ingredient in various health or pharmaceutical products, making eucalyptus oil a product that is much sought after. The need for eucalyptus oil is currently increasing with the development of variations in the use of eucalyptus oil. This study aims to determine the economic valuation of eucalyptus trees (Melaleuca leucadendron) on the economy in Tanjung Bonai Aur, Sumpur Kudus District, Sijunjung Regency. The methods used in this research are observation, interview and respondent methods. The analysis used in this research is descriptive analysis and quantitative analysis. Based on direct observation there are 100 eucalyptus trees in the Tanjung Bonai Aur LPHN area. This study used an interview method involving 25 respondents consisting of 16 male respondents and 9 female respondents. Based on data analysis to determine the Total Economic Value (NET) consisting of direct use value in the form of essential oil utilization, indirect use value in the form of erosion control, and inheritance value in the form of eucalyptus distillation equipment consisting of 1 boiler with 2 reactor units. Then the Total Economic Value (NET) obtained is Rp. 66,506,294 which consists of: direct use value of RP. 28,080,000/year, indirect use value of RP. 20,426,294/year, and inheritance value of RP. 18,000,000/year. Keywords: Economic Valuation, Eucalyptus, LPHN.